The Role of Illness Perceptions, Coping, and Self-Efficacy on Adherence to Precautionary Measures for COVID-19 - Chong, Yuen Yu; Chien, Wai Tong; Cheng, Ho Yu; Chow, Ka Ming; Kassianos, Angelos P.; Karekla, Maria; Gloster, Andrew T. (My University, 2020)
As the novel coronavirus disease 2019 (COVID-19) pandemic continues, engaging the public in adherence to precautionary measures for preventing COVID-19 spread or infection becomes difficult. The present study aims to extend our understanding of how illness perceptions, coping, and self-efficacy affect adherence to precautionary measures among the public. An online survey was administered between April and June 2020 to a sample of 514 Hong Kong citizens. Variables considered were illness perceptions toward COVID-19, problem-solving, avoidance-based coping, self-efficacy, as well as adherence to precautionary measures including physical distancing, limiting unnecessary travelling, and washing hands regularly with soap and water. Adjusted structural equation model showed that illness perceptions toward COVID-19 had significant direct effect on their adherence to precautionary measures (unstandardized β = 0.50, [95% CI, 0.28, 0.80], p = 0.001), and indirect effects through avoidance-based coping (β = -0.10 [95% CI, -0.26, -0.01], p = 0.016) and self-efficacy (β = -0.10, [95% CI, -0.18, -0.01], p = 0.025). These results imply that apart from emphasizing the health hazards of a novel infectious disease, an effective public health intervention and crisis communication should address avoidance-based coping and self-efficacy of the public in adherence to precautionary measures for COVID-19.
Keywords: COVID-19; Adherence; Public health; Avoidance; Coping